Pleural effusion as a rare presentation of foreign body aspiration. (2021) - Okamoto, Shouichi; Takamori, Mikio; Yamamoto, Miake; Murata, Kengo; Wada, Akihiko
Abstract: Unsuspected, non-asphyxiating, aspirated foreign body often masquerades as unresolved pneumonia, bronchiolitis or bronchial asthma. We report herein an 82-year-old, male patient with pleural effusion. Although the patient received the diagnosis of heart failure and treatment with diuretics, the pleural effusion remained, and a productive cough and a low-grade fever developed. Thoracentesis showed an exudative effusion, and chest computed tomography revealed a pill-like object in the right bronchus intermedius. The foreign body proved to be an iron pill, and the patient finally died from obstructive pneumonia due to severe mucosal damage caused by the pill. The present case emphasizes that foreign body aspiration may mimic not only respiratory but also cardiovascular diseases and should be suspected if the treatment of the initially diagnosed condition fails to ameliorate the patient's condition.